The use of some non-steroidal anti-inflammatory analgesics after surgical treatment of difficult eruption of delayed teeth and chronic odontogenic sinusitis - Tymofeiev, О. О.; Maksymcha, С. В.; Tymofeiev , О. О.; Cherednichenko, А. М.; Yaryfa, М. О.; Chaikovskyi, І. Г.; Blinova, В. П.; Myroshnyk, А. О.; Ripa , В. М.; Fil , В. Г. (Actual Dentistry, 2024)
Purpose: The aim of the study is to compare the effectiveness of using NSAIDs with the active ingredient – ketorolac tromethamine and nimesulide to eliminate postoperative pain in maxillofacial surgery Methods: Examination was carried out on 198 patients. All experimental patients were divided into 4 groups. The first group included 54 patients with difficult eruption of wisdom teeth, who underwent excision of the hood of soft tissues located above an incompletely erupted wisdom tooth. The second group included 49 patients who underwent atypical removal of a decayed wisdom tooth. The third group included 57 patients with atypical removal of dystopian and ratinized teeth. The fourth group included 38 patients who underwent gentle sinus surgery with local plasty of the oro-antral connection in chronic odontogenic sinusitis. Results: The results of the examination of patients after surgical interventions in the maxillofacial region indicate that the drugs nimesulide and «Ketanov» are highly effective and safe drugs, which we recommend using to eliminate pain and treat inflammatory symptoms. Conclusions: The drug nimesulide is effective after surgical interventions on soft tissues. The drug «Ketanov» has a more pronounced and long-lasting analgesic and anti-inflammatory effect, we recommend its use in extensive operations in the maxillofacial area, which include interventions on soft and bone tissues at the same time.